Characteristics of Functional Salt from Green Seaweed Ulva lactuca - Raudhi Kurniawan; Nurjanah; Agoes M.Jacoeb; Asadatun Abdullah; Rizsa Pertiwi (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Ulva lactuca is a potential source of functional salt. The production of the functional salt is limited by the fishy smell of the product. The purpose of this research was to determine the concentration of activated charcoal that can reduce the fishy odor of seaweed salt. The functional salt was extracted using activated charcoal at 0.5; 0.75; 1; 1.25 and 1.5%. The sensory and functional properties of the salt including mineral content, Na: K ratio, NaCl levels, total phenol and antioxidant activity were characterized. The sensory tests showed that 1.5% activated charcoal improved salt's consumer acceptance. The selected functional salt contained Na 91.00±1.28 g/kg; K 44.88±0.06 g/kg with a Na: K ratio of 2.03±0.03. This salt also contained NaCl 9.08±0.42%; total phenols of 13.72±0.19 mg GAE/g extract and antioxidant activity expressed by IC50 1681.27±3.80 mg / L.